2005
DOI: 10.2136/sssaj2005.0522
|View full text |Cite
|
Sign up to set email alerts
|

Soil Lime Requirement by Direct Titration with a Single Addition of Calcium Hydroxide

Abstract: et al., 1990; Owusu-Bennoah et al., 1995) used for comparison with other procedures to determine the LR. Direct titration of acid surface soils is often used to measure soil Studies by Magdoff and Bartlett (1985) indicated that acidity. However, titration has not been used for routine determinathe titration curves of acid surface soils are approxition of the lime requirement (LR) in soil testing laboratories, because it is too time-consuming, requiring multiple additions of base and mately linear. Weaver et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 11 publications
1
52
0
Order By: Relevance
“…‡ Theoretical soil pH after application and reaction of lime. the University of Georgia to determine the LR from the two-point Ca(OH) 2 method proposed by Liu et al (2005). This allowed comparison between full titration curves (with no corrections) and a two-point titration.…”
Section: Field Soils Sixty-day Incubationmentioning
confidence: 99%
See 1 more Smart Citation
“…‡ Theoretical soil pH after application and reaction of lime. the University of Georgia to determine the LR from the two-point Ca(OH) 2 method proposed by Liu et al (2005). This allowed comparison between full titration curves (with no corrections) and a two-point titration.…”
Section: Field Soils Sixty-day Incubationmentioning
confidence: 99%
“…A new method proposed by Liu et al (2004Liu et al ( , 2005 is also free of hazardous chemicals and uses a titration with 0.022 M Ca(OH) 2 to measure the pH buffering capacity of a soil with a single addition of Ca(OH) 2 . They found that an average of 80% of the LR from their standard 3-d Ca(OH) 2 incubation was measured by using a Ca(OH) 2 titration.…”
mentioning
confidence: 99%
“…Such a linear response was observed in several studies (Liu et al, 2005;Hoskins and Erich, 2008;Wolf et al, 2008). A target pH of 6.5 is recommended for corn and soybean in Iowa (Sawyer et al, 2002).…”
Section: Sitementioning
confidence: 68%
“…Therefore, work has been done to develop alternative methods for determining lime needs without using hazardous chemicals. Some researchers have tried direct titrations using single additions of Ca(OH)2 (Liu et al, 2005;Kissel et al, 2007;Thompson et al, 2010). The modified Mehlich buffer was developed by Hoskins and Erich (2008) primarily to overcome the drawbacks of the SMP buffer procedure (i.e., tmstable buffer pH readings, rapid electrode degradation, poor precision of results, and the production of hazardous waste in the laboratory).…”
mentioning
confidence: 99%
“…Most of the buffers used to estimate LR contain hazardous components, including hexavalent chromium and barium, and there is a general trend toward developing buffers without these hazardous constituents (Hoskins 2005;Sikora 2006) or alternative methods of LR determination (Liu et al 2005). The Sikora and modified Mehlich buffers were designed to mimic the SMP and Mehlich buffers, respectively, but without the hazardous constituents.…”
Section: Introductionmentioning
confidence: 99%